Structure-Function Relationship in Patients with High Myopia and Glaucoma: A Comparison Between the Macula, Optic Disc, and Retinal Nerve Fiber Layer - Hilariao, Ana Aurea; Zangarini, Vinicius Henrique; Amorim-Cabral, Camila Lisandra; Pacovska, Mayara Fernanda; Kasahara, Niro (Universitas Airlangga, 2026)
Introduction: Optic disc appearance in high myopic patients often confounds the diagnosis of glaucoma. Purpose: To compare the structure-function correlation between two optical coherence tomography (OCT) protocols, the ganglion cell complex (GCC), and the circumpapillary retinal nerve fiber layer (RNFL) in patients with high myopia and glaucoma and suspects. Methods: This was a retrospective, cross-sectional study conducted in a private hospital. The electronic files of patients with high myopia (> -6.00 (D) spherical diopter) and glaucoma or suspects were reviewed. GCC thickness, average RNFL thickness, and vertical cup-to-disc ratio (C/D) values obtained from the OCT were correlated with the mean deviation (MD), pattern standard deviation (PSD), and visual field index (VFI) obtained by automated perimetry. Correlation was assessed using multivariable regression analysis. Results: The study included 54 eyes from 27 patients. The mean age of participants was 53.7 ± 11.3 years; 12 were male and 15 female. The mean spherical equivalent was -9.3 ± 3.9 D. The strongest correlation was between GCC and MD, after controlling for confounders (0.196, 95% CI 0.048 to 0.164, P = 0.008). Conclusions: In this small cohort of high myopic glaucoma patients and suspects, the structure-function correlation was stronger with GCC and MD than with C/D, RNFL, and functional parameters. This observation highlights the importance of assessing the macula in glaucoma and high myopia patients.